Ethnic Conflict in the Indian Subcontinent: Assessing the Impact of Multiple Cleavages. (December 2019) - Das, Soham
Abstract: As majoritarian electoral politics and religious conservatism are rising in the major multi-ethnic South Asian countries, such as India and Pakistan, the events of mob lynching, ethnic clashes and targeting non-plural and minority communities are becoming more frequent. This article analyses which cleavages of marginalisation make some ethnic groups prone to violent social movements vis-a-vis others. Theoretically, through social constructivism and horizontal inequality, the study argues that socioeconomic condition, religion and language are the three broad cleavages that influence political behaviour of ethnic groups. Explicating the theory about underlying versus facilitating conditions of ethnic–civil conflicts, this article examines the prerequisites of ethnic conflicts. Thereafter, it evaluates which single cleavages and combinations of the aforementioned cleavages increase the probability of conflict occurrence in the Indian subcontinent. The argument is empirically evaluated on a sample of 60 ethnic groups of the Indian subcontinents over the period of 1947–2013. We find that groups affected by reinforcing cleavages of religious and economic marginalisation, and religious, economic and lingual marginalisation have engaged in active violence over the period of our study. Additionally, the reinforcing cleavages of language and economy, and language and religion are associated with sporadic violence. Apart from the combined effects, we find that the ethnic groups facing economic disadvantage alone can also engage in violence.